Effectiveness of riamilovir in preventing respiratory viral infection among young people from organized collectives - Konstantin V. Kozlov; Oleg V. Maltsev; Kristina V. Kasyanenko; Vitalii S. Sukachev; Andrei V. Saulevich; Sergey S. Karyakin; Alexey D. Dubrovin; Roman N. Smirnov (Терапевтический архив)
Aim. To evaluate the efficacy of the antiviral drug riamilovir (trade name – «Triazavirin®») for the prevention of SARS-CoV-2 infection (COVID-19) and other acute respiratory viral infections in young people from organized groups.